Measuring the performance of higher education among state universities and colleges in SOX Region, Philippines - Ernie C. Cerado; Nathaniel D. Naanep (Institute of Advanced Engineering and Science, 2023)
As state universities and colleges (SUCs) in the Philippines are confronted by tough competition for limited resources, and to show to government legislators that subsidy on tertiary education meaningfully produces significant returns; thus, they are pressed to undertake continuous improvement for optimum performance. Practically, measuring the performance of SUCs is essential to identify critical issues, make informed decisions, and enhance higher education policies. In this descriptive-evaluative study, the institutional performance was measured using the Fiscal Year 2016 SUC levelling instrument of department of budget management (DBM) and the commission on higher education (CHED), covering four key result areas (KRA): i) Relevance and quality of teaching; ii) Research productivity, iii) Community engagement; and iv) Resources management. Respondents included 217 faculty members and 24 deans from the four SUCs in SOX Region, Philippines. A combination of descriptive and inferential statistics was used in the data analysis. Results indicated that the SUCs fared randomly in the leveling scheme. SUC-Y got excellent performance, while SUC-X tailed at a very satisfactory rating in all areas. Statistical tests showed that SUC-Y was relatively superior to the other SUCs. Moreover, the performance of SUC-W and Z were comparable and found as the lowest in the group. The major issues and challenges affecting institutional performance include multi-tasking or designation of faculty to administrative positions, inadequate laboratory facilities, and limited online modality for laboratory subjects.